Cladding of Mg Alloy with Zr Based BMG Alloy - A. K., Prasada Rao; Shu Yin, Oh; M. K., Faisal; N. J., Kim (IOP Publishing, 2016)
In the present work, an attempt has been made to clad AZ31 magnesium alloy with Zr-based bulk metallic glassy alloy (Vit-1), by casting method. The interface studies conducted using SEM-EDS line scan indicate that a good bond is formed at the clad interface of Zr and Mg. And the mechanism involved is discussed herein.